Penilaian Kesuksesan Penerapan Xero Accounting Software Dengan Model UTAUT dan Delone & McLean - Pratiwi, Ni Putu Diah; Ariyanto, Dodik; Putra, I Nyoman Wijana Asmara; Mimba, Ni Putu Sri Harta (E-Jurnal Akuntansi; Vol 32 No 2 (2022), 2022)
This research is motivated to use the UTAUT and DeLone & McLean models to see how the system users respond, especially the application of Xero Accounting. The research was conducted at a restaurant in Badung Regency - Bali. The sampling technique used is purposive sampling. The number of samples in the study were 174 respondents. Collecting data using a questionnaire. Data analysis in this study used Partial Least Square (PLS). The results of testing the UTAUT and DeLone & McLean model variables consisting of performance expectancy, effort expectancy, and system information quality that affect interest in using Xero Accounting. The variables in the UTAUT and Delone & McLean models are performance expectancy, effort expectancy, facilitating conditions, and system information quality that affect system user satisfaction. The variables of usage interest and user satisfaction have an effect on individual performance. The practical implications of this research provide a new perspective on the use of Xero Accounting in restaurant companies. Keywords: UTAUT; Delone & Mclean; Xero Accounting Software.